DIALEKTIKA FEMINIS INDONESIA TERHADAP UNDANG-UNDANG POLIGAMI - Ivan Majeda; Musolli Musolli (SHAKHSIYAH BURHANIYAH: Jurnal Penelitian Hukum Islam, 2023)
This study aims to trace Husein Muhammad’s reason thinking, Indonesian feminist Kyai in the case of licensing polygamy according to the Compilation of Islamic Law. Husein Muhammad is one of the pesantren kiai who is intense in gender issues. The idea offered by Husein Muhammad is reinterpretation of gender-biased legal issues in the hope that it can be used as a guide and guide in dealing with particular problems at the present time. This study seeks to unravel the views of KH. Husein Muhammad on gender justice in polygamy permits. This research is a qualitative research literature (library research). The technique used in analyzing the data in this study, using descriptive-analytical method, to describe in general the thoughts of Husein Muhammad. The data for this research are books written by Husein Muhammad and interviews with him. This study concludes that Husein Muhammad's method of thinking in rejecting the rules for licensing polygamy according to the rules of the Compilation of Islamic Law is based on the concepts of selection (intiqo-iy) and exploration (ijtihad). These two concepts are oriented towards the concept of protecting and providing a sense of justice for women which can be integrated into Indonesian positive law. Keywords: Feminist kyai, Critical reasoning, Polygamy laws Daftar Pustaka Al Amin, Habibi. "Guardians Concept in Qur'an Perspective." Shakhsiyah Burhaniyah: Jurnal Penelitian Hukum Islam 6.1 (2021): 95-114. Al Amin, Habibi. "Penciptaan Adam; Mendialogkan TafsiR Marah Labid dengan Teori Keadilan Gender." An-Nuha: Jurnal Kajian Islam, Pendidikan, Budaya Dan Sosial 1.1 (2014): 17-44. Al Amin, Habibi. "Tafsir Sufi Lataâ€™ if al-Isyarat." SUHUF 9.1 (2016): 59-77. Al-Husaini, Taqiyuddin Abi Bakar Muhammad, Kifayatul Akhyar Fi Halli Ghayatil Ikhtishar, Indonesia: Haramain Jaya Indonesia, 2005. Al-Kasani, Alauddin Abi Bakar bin Mas’ud, Bada’i Sana’i Fi Tartibi Syara’i, Beirut: Darul Kutub, 2003. Al-Maliki, Alwi Abbas Ibanah al-Ahkam, Beirut: Darul Fikr, 1996. Al-Qozwaini, Abdullah Muhammad bin Yazid, Sunan Ibnu Majah, Beirut: Darul Fikr, tt. Al-Syairazi, Abu Ishaq Ibrahim bin Ali, Al-Muhadzdhab, Beirut: Darul Kutub, 1995. Al-Syarkhasi, Syamsuddin Abu Bakr Muhammad, Al-Mabsuth, Beirut: Darul Makrifah, tt. Al-Zuhaili, Wahbah, Terj. Agus Effendi dan Bahruddin Fananny, Zakat Kajian Berbagai Madzhab, Bandung: PT Remaja Rosdakarya, 2008. _________________, Terj. Abdul Hayyie al-Kattani, dkk, Fiqih Islam Wa Adillatuhu, Jakarta: Gema Insani, 2011. An-Nawawi, Abu Zakaria Muhyiddin bin Syaraf, Al-Majmu’, Beirut: Darul Fikr, tt. Arikunto, Suharsimi, Prosedur Penelitian Suatu Pendekatan Praktek, Jakarta: Rineka Cipta, 2006. As’at, Kamran dkk, Fiqh Ibadah, Jakarta: Amzah, 2009. Ash-Sajastany, Abi Dawud Sulaiman Ibn Ash’as, Sunan Abi Dawud, Beirut: Darul Fikr, 1994. Ash-Shiddieqy, M. Hasbi, Pedoman Zakat, Semarang: Pustaka Rizki Putra, 2009. Ash-Syaukani, Muhammad bin Ali bin Muhammad Nailul Author, Beirut: Darul Fikr, 1983. Taufiqurrahman, Zaky Fajar, and Habibi Al Amin. "Desain Pembelajaran Literasi Kitab Kuning Melalui Metode Sorogan dalam Meningkatkan Pemahaman Agama Islam." Syntax Literate; Jurnal Ilmiah Indonesia 6.2 (2021): 1467-1474.